Interreligious Living in the Context of South Africa - Lategan, Bernard C. (Interreligious studies and intercultural theology, 2023)
Interreligious dialogue presupposes conceptual articulation and verbal communication. This article focuses on a different and less prominent expression of interreligiosity, namely interreligious living. Instead of relying on conceptual and verbal instrumentalities, interreligious living speaks through action and practice. Because of the embodied nature of this phenomenon, it is highly contextual in nature and consequently manifests itself in diverse ways in different social settings. A tentative exploration of some examples in the South African context raises a series of basic questions: Does interreligious living complement interreligious dialogue or does it represent an alternative to (or even a form of protest against) it? Does interreligious living gloss over or underplay the real differences that exist between religions and interreligious dialogue sees as an important issue to address? Does interreligious living presuppose a common, overarching cause which invokes it in the first place? The article concludes with a plea for more extensive research into interreligious living as a social phenomenon in its own right.